Research and Practice on Progressive Collapse and Building Strength in 2019 and 2020 (Journal of Civil Engineering Researchers, 2021)
A chain reaction or collapse-spreading in which, under certain causes, local damage occurs in a relatively small area of thestructure and under certain conditions this local damage spreads to other parts of the structure and ultimately leads to overallcollapse of the structure is called progressive collapse. The main feature of this phenomenon is that the final collapse is notcommensurate with the initial collapse; severe incidents such as terrorist attacks, vehicle collisions and explosions, etc. oftendamage the building and collapse in one or more vertical bearing parts leads to a serious threat. The following article providesan overview of the main research and developments in 2019 and 2020 regarding progressive collapse such as progressivecollapse assessment, experimental testing, and numerical modeling.
Keywords: progressive collapse; RC frames; beam connection; column loss scenario; steel frames; flange-plate connection